Validity of Electronic Worksheet (E-LKPD) Based on PBL Model to Train Creative Thinking Skills on Acid-Base Material - Ainiah, Errisya Nur; Yonata, Bertha (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Creative thinking skills are important to train students to face the challenges of the 21st century and include higher order thinking skills. In addition, the independent curriculum provides freedom to think and innovate in learning. Therefore, one of the efforts to train creative thinking skills is to use relevant learning media, namely E-LKPD based on the Problem Based Learning (PBL) model. The purpose of this research is to produce PBL-based E-LKPD to train the creative thinking skills of grade XI students on acid-base material that is feasible to use, in terms of validity.Â  This research model is guided by Thiagarajan's 4D model (Define, Design, Develop, and Disseminate). However, the research only reached the development stage (Develop) to determine the validity of the product because there were limitations in time, funds, and energy. Validation was conducted by 3 validators to measure the content and construct validity of the developed E-LKPD. The results showed that the validity of the E-LKPD was considered valid based on the median score of content validity of 4 with a valid category and construct validity of 5 with a very valid category.